Book phenomenon in library philosophy and library research - Sporane, Baiba (Knygotyra, 2024)
The book plays the most important role in the development of the culture of our civilization—the mental heritage of all generations for all generations is contained in books. The most important feature of the book is that it serves as a knowledge keeper ("the brain on the shelf"), because the human being is a creature who remembers and is aware of their history, who thinks historically. The book, in the broadest sense (independently of its material form—printed, electronic, or another form), is an accumulative form of human actions and can be characterized as a social phenomenon, as a sign and symbol, and one of the forms of social memory—i.e., informational memory. A phenomenon in philosophy is a rare, unusual thing existing only in consciousness, the subjective content of our consciousness. The book as a phenomenon in library philosophy could be described as a phenomenon of culture and social environment, maintaining its existence within itself, discovering and expressing itself independently, without merely describing the book outwardly, but explaining it and finding the essential point that determines the significance of the book’s essence. The real existence of the book versus the book as a phenomenon—have we reached the end of the book? Phenomena exist in the deepest layers of consciousness, discovering beings, realities, and ideas, not material forms. A person can comprehend, experience, and understand a book’s internal being, valuing the book as a phenomenon, not just as a piece of material culture. Communication with a book is the highest form of intellectual development. This highest form can be examined from various perspectives: epistemological, axiological, hermeneutical, and semiotic. The book is the mirror of those who look into it (and who create this mirror too), and its idea can be found in the human brain. Therefore, the book is very closely connected with humans and society as a tool of human inter-subjective action. Another aspect is the book as a tool, a communicative tool, self-created as the result of human mental activities (like tools such as a spade or axe, but with different goals) for a specific goal—social communication (including religion, philosophy, fiction, thinking, etc.) and historical memory. The book, as a communicative element (separated from a tool like a spade that digs soil), digs into the consciousness of the user/reader, and, created by humans, transforms this same human. Is it possible that this same transformed human will favor the death of the book? The author’s opinion is that it could happen, but only in terms of form, not in essence. The end of the book, the printed text, and old-style reading is a real possibility, not an academic joke or a post-structuralist conceit. How the book will look in the near future, whether it will still be called a "book," and whether changes in its historical form will change the name "book" and its essential nature, we will see very soon. The author’s opinion is that changes in material form cannot change the philosophical and social existence of the book or its essential nature.